WOMEN'S EMPOWERMENT IN RURAL ANDHRA PRADESH: CHALLENGES, STRATEGIES, AND OUTCOMES - Bindu, Janga; Madhavapeddy, Sneha; Reddy, G Raghupal; Khan, Irfan Ali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this study, we explore the complex path that has led to rural women's empowerment in Andhra Pradesh, India. It elucidates the complex issues that women in these areas confront and investigates the actions that have been taken to empower them. This research adds to the larger knowledge of gender equality initiatives in a varied and developing rural terrain by an in-depth analysis of socioeconomic inequalities, cultural dynamics, and policy interventions. This research provides important insights into the transformational potential of women's empowerment in rural Andhra Pradesh by studying the effects of education, health, local government, livelihoods, and cultural factors. These results highlight the need for strategies that take into account the interplay of gender, culture, and social and economic conditions in order to bring about long-term improvements for women's status in this area.